Exhibition as Site of Transgression: An Interview with Sandi Hilal and Alessandro Petti (DAAR - Decolonizing Architecture Art Research) - Alessandro Paolo Lena (Museum, Materials and Discussions)
In light of the thematic dossier presented in the inaugural issue of MMD, this section dedicated to experience and publics features an interview with architects Sandi Hilal and Alessandro Petti, founders of DAAR – Decolonizing Architecture Art Research.